PENGARUH RISIKO KREDIT (NPL), RISIKO LIKUIDITAS (LDR) DAN RISIKO OPERASIONAL (BOPO) TERHADAP KINERJA KEUANGAN (ROA) PADA PT BANK MANDIRI (PERSERO) TBK PERIODE 2015 – 2024 - Seni, Seni Putri Harefa; Hasanudin Hasanudin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of Credit Risk, Liquidity Risk, and Operational Risk on the Financial Performance of PT Bank Mandiri (Persero) Tbk for the period 2015 –2024. Credit risk is measured by Non-Performing Loans (NPL), liquidity risk is measured by the Loan to Deposit Ratio (LDR), and operational risk is measured by Operating Costs to Operating Income (BOPO), while financial performance is measured by Return on Assets (ROA). The research data were obtained from the officially published annual financial reports of PT Bank Mandiri (Persero) Tbk. This study uses a descriptive quantitative method with a sample of 10 annual financial reports for the period 2015–2024. The data analysis technique uses simple linear regression and multiple linear regression with the help of SPSS software version 26. Hypothesis testing is carried out using the T-test, F-test, and coefficient of determination test after first conducting the classical assumption test. The results of the T-test show that Credit Risk (NPL) has a negative and significant effect on Financial Performance (ROA) with a calculated T-value of -4.793 > T-table 2.306 and a significance value of 0.001 < 0.05. Liquidity Risk (LDR) does not have a significant effect on Financial Performance with a calculated T-value of 1.145 < T-table 2.306 and a significance value of 0.285 > 0.05. Operational Risk (BOPO) has a negative and significant effect on Financial Performance with a calculated T-value of -6.379 > T-table 2.306 and a significance value of 0.000 <0.05. Simultaneously, Credit Risk, Liquidity Risk, and Operational Risk have a significant effect on Financial Performance with a calculated F-value of 15.171 > F-table 4.76 with a significance level of 0.003 < 0.05. At PT Bank Mandiri (Persero) Tbk.